Literature Review: The Role Of Radio During Pandemic For Socialization Efforts In New Normal Era - Bethy, Rayya; Pawito, Pawito; Utari, Prahastiwi (Journal of International Conference Proceedings, 2023)
The government has prepared all levels of society to face the new normal era. Then forwarded by each local government by issuing policies and appeals related to health protocols in the new normal era. In this case, the public must also receive accurate and correct information from the government. Radio as one of the mass media, has an important role in supporting the dissemination of information about some of the new normal protocol policies. The purpose of this article is how the role of radio in socializing the new normal to the community. Radio as an extension of the government's arm to provide information whose accuracy can be accounted for and is expected to provide education to the public to implement health protocols in the new normal era.